2020
DOI: 10.32598/cmja.10.3.1020.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupressure on Stress and Anxiety of Patients with Multiple Sclerosis: A Sham-controlled Randomized Clinical Trial

Abstract: Objective: Stress and anxiety are common in patients with Multiple Sclerosis (MS). These complications exacerbate the symptoms of MS. This study aims to evaluate the effect of acupressure on stress and anxiety of MS patients. Methods: In this randomized clinical trial, participants were 106 MS Patients referred to Multiple Sclerosis Society in Mashhad, Iran. After signing an informed consent form, they completed a demographic form and stress, and the Depression Anxiety Stress Scale - 42 items (DASS-42). Then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Modulating neurohormonal responses in the hypothalamic, pituitary, and adrenal axes and increasing serotonin levels can regulate the secretion of cortisol and cause relaxation. Also, serotonin through facilitating the secretion of gammaaminobutyric acid (GABA) leads to calming and modulating behavioral responses [59]. Moreover, reducing the activity of the sympathetic system and the secretion of endorphins play important roles in calming the person [60].…”
Section: Discussionmentioning
confidence: 99%
“…Modulating neurohormonal responses in the hypothalamic, pituitary, and adrenal axes and increasing serotonin levels can regulate the secretion of cortisol and cause relaxation. Also, serotonin through facilitating the secretion of gammaaminobutyric acid (GABA) leads to calming and modulating behavioral responses [59]. Moreover, reducing the activity of the sympathetic system and the secretion of endorphins play important roles in calming the person [60].…”
Section: Discussionmentioning
confidence: 99%
“…Acupressure, in particular, stands out as a self-administered technique without the need for external assistance [10,11]. Specific acupressure points, including Shenmen, Hegu, and the third eye, have been identified as effective in reducing both pain and anxiety [12,13]. Research conducted in Iran demonstrated the effectiveness of acupressure in controlling pain during arterial sheath removal in patients undergoing angioplasty [14].…”
Section: │ Introductionmentioning
confidence: 99%